BRIDGING EMOTION AND PRACTICE: REFLECTION IN THE ART OF COMPASSIONATE CAREGIVING - Ana, Beatriz da Silva; João, Carlos Ferreira Souza (International Journal of Contemporary Health Sciences and Technology, 2025)
The concept of palliative care, rooted in the historical use of the term "pallium" as a protective cloak, embodies a profound mission of protection and accompaniment for individuals facing life-threatening illnesses. The World Health Organization's (WHO) 2002 definition of palliative care underscores its role in enhancing the quality of life for patients and their families confronting the challenges associated with life-threatening conditions. This approach centers on the prevention and alleviation of suffering through early identification, impeccable assessment, and the treatment of not only physical pain but also psychological and spiritual distress. When confronted with the impending reality of death, patients express clear preferences that align with the core principles of palliative care. They seek knowledge about what to anticipate, the sense of preparedness for the journey ahead, control over pain and symptoms, and the preservation of meaningful connections with their loved ones. Ultimately, they strive for a sense of fulfillment, a conclusion of life's mission